The Effect of E-Service Quality E-Word of Mouth on Purchasing Decisions at the PF Store Pematang Siantar - Akbar, Agasi; Yunita, Nindya; Aramita, Finta (Management Department Universitas Islam Negeri Sumatera Utara, 2024)
This research investigates the influence of E-Servqual and E-WoM on purchasing decisions in the context of social media-based e-commerce, with a case study of PF Store Pematang Siantar, an Instagram-based fashion retailer in North Sumatra, Indonesia. As social commerce through Instagram becomes increasingly prevalent in regional markets, understanding the factors that influence consumer purchasing decisions is crucial for business sustainability. The study employed a quantitative approach with 98 respondents, selected through the Slovin formula from 5,050 Instagram followers of PF Store as of May 2024. The findings reveal significant contributions to understanding consumer behavior in social media-based retail. E-Servqual (X1) demonstrated a greet impact on purchasing decisions, with t-count value is greater than the t-tabel at a significance level of 0.02. Similarly, E-WoM (X2) showed a stronger positive influence at a significance level of 0.03. The simultaneous effect of both variables was confirmed through F-test results with a significance value of 0.001, indicating their crucial role in driving consumer purchasing decisions in social commerce platforms. These results provide valuable insights for small and medium-sized enterprises utilizing Instagram as their primary e-commerce platform, particularly in regional markets. The study highlights the importance of maintaining high-quality electronic services and managing customer feedback effectively in social media-based retail environments. Keywords: E-Servqual, E-WoM, Purchasing Decisions